Fintech Technology Strategy for Financial Management of PT Astra Indonesia Company - Daming , Sudirman; Widyawati, Widyawati (Economics and Digital Business Review, 2023)
Study This aiming For analyzing fintech technology strategies and their impact to management finance at PT Astra Indonesia. In the increasingly digital era advanced , fintech has appear as solution important For increase efficiency operational , transparency , and decision making decision data -based in the company . Through implementation of fintech, PT Astra Indonesia succeeded increase efficiency of financial processes , which contributes to the management more cash flow good . Access to real-time data allows management For make more decisions​ fast and accurate , and minimize risk lack liquidity . In addition , fintech also strengthens transparency and internal control , which in turn reduce potential abuse and increase integrity report finance . However , the challenge in implementation technology this , like resistance culture employees and concerns about data security , need overcome For maximize benefits of fintech. Research This conclude that although there is obstacles , the implementation of fintech at PT Astra Indonesia provides impact significant positive​ to management finance , making company more adaptive and competitive in an increasingly competitive market dynamic . In general overall , results study This show that fintech strategies can become effective tool​ For increase management finance , with condition existence support from all parties in​ company as well as effort sustainable For overcome existing challenges .​